My farm friends - Minor, Wendell (New York : G.P. Putnam's Sons, 2011)
Simple, rhyming text describes the characteristics of different farm animals. Includes "Farm friends fun facts" and books and websites for further reading.
003-005.
Keywords: Stories in rhyme; Domestic animals -- Juvenile fiction